Zonas colombianas productoras de caña de azúcar. - Gómez Peña, Jaime Fernando; Sánchez Emers, Orlando; Buenaventura Osorio, Carlos Eduardo; Ranjel Jiménez, Hernando; Ayalde Varón, Guillermo (Instituto Colombiano Agropecuario, 2018)
Caña de azúcar-Saccharum officinarum